Determining the Understanding of Task-Based Language Teaching among the English Teachers of NU Affiliated Colleges in Bangladesh - Munira, Serajum; Sikder, Liton Baron (Green University Review of Social Sciences, 2022)
Though the Non-credit English courses are treated mandatory for all undergraduate students at National University, the students do not appear to take them seriously because the total marks do not contribute to their final grade. Previous studies suggest that Task-Based Language Teaching (TBLT) motivates the students to language acquisition. Therefore, this study attempted to determine the factors of implementing the TBLT in non-major English courses. In TBLT, the teacher engages the learners with a task-based instruction to make them act as if they were using the language in real life. Therefore, TBLT has become more common and recommended as a way forward in ELT. The objectives were to measure the level of understanding of task of TBLT, perceived usefulness of implementing TBLT, and perceived challenges of TBLT. The research involves surveys and fact-finding investigations as certain hypotheses are presupposed. In this study, the random sampling procedure has been maintained to capture all segments of the population such as urban and rural, and divisional city, district level city and upazila level city. A questionnaire was designed to examine Bangladeshi EFL teachers’ understanding and beliefs of task-based language teaching with reference to classroom practice. In the survey, 79 male and 38 female EFL teachers participated. The scores of the males in understanding of tasks in TBLT (M=3.32) than that of the females (M=3.20). While in perceiving the benefits of implementing TBLT, females scored higher (M=4.34) comparing to the males (M=4.25). Both males and females had same scores in terms of perceiving the challenges of implementing TBLT in EFL programs. The results indicate that the level of understanding is lower. As a result, the level of perceived challenges of implementing TBLT is higher. Therefore, in conclusion, this study suggests to emphasize on arranging effective training and workshops for the EFL teachers so that they can understand the task in TBLT. Green University Review of Social Sciences Dec 2021; 7(1-2): 220-235